2019
DOI: 10.1111/1541-4337.12455
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioactive Peptides from Lactic Acid Bacteria: A Sustainable Approach for Healthier Foods

Abstract: Traditional fermented foods where lactic acid bacteria (LAB) are present have been associated with beneficial effects on human health, and some of those benefits are related to protein‐derived products. Peptides produced by LAB have attracted the interest of food industries because of their diverse applications. These peptides include ribosomally produced (bacteriocins) and protein hydrolysates by‐products (bioactive peptides), which can participate as natural preservatives and nutraceuticals, respectively. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 155 publications
2
46
0
7
Order By: Relevance
“…With the recognition of the gut microbiota, probiotics can be used to modify health and disease, even though the exact mechanisms remain unclear. LAB probiotics are widely used in the food industry and have gradually developed into relatively indispensable functional foods that are eaten on a daily basis (Filanniono, Cagno, & Gobbetti, 2018;Venegas-Ortega, Flores-Gallegos, Martinez-Hernandez, Aguilar, & Nevarez-Moorillion, 2019). Studies have shown that LAB can alter the sensation and motility of the gut (Quigley, 2007;Rousseaux et al, 2007), soften the stool, and change secretion, as well as produce lactic acid and/or short-chain fatty acids that can lower the intraluminal pH and promote defecation (Salminen & Salminen, 1997;Waller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With the recognition of the gut microbiota, probiotics can be used to modify health and disease, even though the exact mechanisms remain unclear. LAB probiotics are widely used in the food industry and have gradually developed into relatively indispensable functional foods that are eaten on a daily basis (Filanniono, Cagno, & Gobbetti, 2018;Venegas-Ortega, Flores-Gallegos, Martinez-Hernandez, Aguilar, & Nevarez-Moorillion, 2019). Studies have shown that LAB can alter the sensation and motility of the gut (Quigley, 2007;Rousseaux et al, 2007), soften the stool, and change secretion, as well as produce lactic acid and/or short-chain fatty acids that can lower the intraluminal pH and promote defecation (Salminen & Salminen, 1997;Waller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The proteolytic action of LAB strains can be used to obtain bioactive peptides that could participate as regulators in physiological processes [4][5][6]. Although the antimicrobial, proteolytic, and lipolytic properties of LAB have been extensively reported, the selection of strains that have more than one capacity can lead to the detection of multifunctional LAB strains, as we reviewed previously [42]. Antioxidant activities were demonstrated by the inhibition of the ABTS + and DPPH + radicals, using the supernatants obtained by presumptive LAB fermentation of casein-peptone broth.…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing genera of LAB that are used as probiotics are Lactobacillus , Bifidobacterium , Streptococcus , Enterococcus , and Pediococcus [ 142 , 143 ]. The GRAS status of lactic acid by Food and Drug Administration (FDA) has been extensively utilised in food, dairy, and pharmaceutical industries [ 144 , 145 ]. For instance, Lactobacillus delbrueckii subsp.…”
Section: Potential Of Lactobacillus In Keeping Vagmentioning
confidence: 99%